Enhanced power conversion efficiency in bulk heterojunction solar cell based on new polyazomethine with vinylene moieties and [6, 6]-phenyl C61 butyric acid methyl ester by adding 10-camphorsulfonic acid. (20th March 2015) - Iwan, Agnieszka; Boharewicz, Bartosz; Tazbir, Igor; Filapek, Michal
Abstract: A polyazomethine (PPV-PAZ-DMB) containing vinylene and aliphatic side chains was synthesized by polycondensation method. The structure of polymer was characterized by means Fourier transform infrared (ATR-FTIR), proton and carbon nuclear magnetic resonance ( 1 H, 13 C NMR) spectroscopy and the results show an agreement with the proposed structure. Photovoltaic properties of PPV-PAZ-DMB were studied by constructing bulk heterojunction (BHJ) solar cells with the architecture ITO/PEDOT:PSS/PPV-PAZ-DMB:PCBM/Al, where ITO: indium tin oxide, PEDOT:PSS: poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate). Photovoltaic parameters were analyzed taking into account amount of [6, 6]-phenyl C61 butyric acid methyl ester( PCBM) added to PPV-PAZ-DMB and presence of 10-camphorsulfonic acid (CSA) in active layer. With the weight ratio PPV-PAZ-DMB:PCBM of 1:3 and the presence of CSA, the power conversion efficiency (PCE) of the device reached 0.32% with open circuit voltage Voc  = 0.47 V, short circuit current density Jsc  = 2.91 mA/cm 2 and fill factor (FF) 0.25 under simulated 100 mW/cm 2 AM 1.5 G irradiation. It is showed that the PCE of device with CSA was 40 times higher than that of the device without CSA. Devices were additionally tested by electrochemical impedance spectroscopy. An influence of CSA as a dopant on absorption wavelengths, energy gap and HOMO-LUMO levels was investigated.